Mental Health Conditions Among E-Learning Students During the COVID-19 Pandemic - Anna Rutkowska; Błazej Cieślik; Agata Tomaszczyk; Joanna Szczepańska-Gieracha (Frontiers in Public Health, 2022)
AimThe COVID-19 pandemic has forced the education system to undergo changes, which have also affected universities. E-learning became the main form of education, reducing interpersonal contacts, which could affect the mental wellbeing of students. The aim of this study was to investigate the prevalence of depressive symptoms and the level of perceived stress during e-learning among Polish students and to identify the factors for predicting higher levels of depression symptoms.MethodsThe study included 753 participants with a mean age of 22.47 (±4.02) years. The Perception of Stress Questionnaire (PSQ) and Beck Depression Inventory (BDI-II) were used to measure the severity of stress and level of depression. Furthermore, our own survey was used to assess the impact of e-learning on various aspects of life. To examine how much stress can explain a statistically significant amount of variance in depression, three-step hierarchical multiple regression was used. In addition, our own questionnaire was used to assess the impact of e-learning on education, social contacts and technical abilities.ResultsA total of 58% of the students characterized by an increased level of stress. 56% show symptoms of depression and 18% of the participants had suicidal thoughts. The most significant predictor of depression is high stress levels and factors related to e-learning: isolation from friends and acquaintances, negative impact on level of knowledge, reduced motivation to learn, and worsening grades. This predictors may explain about 66% of the variance of depression.ConclusionUniversities should implement interventions and educational programmes, providing ad hoc assistance in the form of individual or group meetings with a psychologist (also in a remote form) and organizing workshops and webinars on strategies for managing stress.